Effects of Salinity on Yield and Postharvest Quality of Tomato (Lycopersicon Esculentum Mill.) - Ali Ahmed Al Eryani, Abdul Raqeeb (2004)
The effects of salinity on the yield and chemical composition of tomato (Lycopersicon esculentum Mill.) fruits produced in soilless culture under protected environment were investigated. Two experiments were carried out at Hydroponic Complex, Crop Science Department, Faculty of Agriculture, Universiti Putra Malaysia. Increasing salinity (EC) from 2 m~cm-('control) to 6 m~cm-l'i nearly reduced total yield, size, firmness and water content of tomato fruits, and dry weights of roots and shoots of plants. The incidence of blossom end rot (BER) was higher at high salinity level as a consequence of deficiency of Ca content, which was found to decrease with increasing salinity levels. On the contrary, high salinity conditions resulted in increasing total soluble solids, carbohydrates (fructose, glucose, sucrose), titratable acidity and ascorbic acid (Vitamin C) concentrations and dry matter content of tomato fruits. The redness (a*) values gradually increased with increasing salinity level from ECs 3 to 6 m~m-', whereas the lightness (L*) and yellowness (b*) values decreased. These observations indicated that it is possible to obtain a good quality tomato fruits with acceptable yield reduction at EC 4.5 m~cm-I. Salinity affected both shelf life of tomato fruits stored at ambient temperature (2 1°C) or in cool condition (15°C) with relative humidity (RH) between 48-66% and 91-92%, respectively. There was a negative relationship between salinity and fruit shelf life, probably due to an increase in polyglacturonase activity, which enhances softening and hence causes shorter shelf life. In another experiment, both high (6 m~cm- 'a)n d moderate (3 mscm-') salinities were applied at different growth stages of plants development. Saline irrigation at EC 3 m~cm- during late developmental stages (onset of ripening) improved the quality of the fruits with acceptable yield reduction (fresh weight, number and size of fruits). In general, maintaining the proper ECs 3 and 4.5 mscm-' appplied at onset of ripening and flowering stages, respectively resulted to in an acceptable yield reductions and high quality products.